2014
DOI: 10.1007/s00011-014-0711-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-related element gene expression pattern differs between microglia and macrophages during inflammation

Abstract: Although the function and the gene expression levels of histone modification enzymes showed a similar pattern in microglia and macrophages during inflammation, the expression of transcription-related elements in both cell types showed a completely different pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…They play a critical role in innate immunity, and they contribute to the initiation of adaptive immunity by recruiting other immune cells 34 . Recent studies have confirmed that macrophages were involved in anti-inflammatory processes and bone remodeling 35 , 36 . In this study, we found that ASA treatment inhibited macrophage polarization to the LPS-induced macrophages.…”
Section: Discussionmentioning
confidence: 94%
“…They play a critical role in innate immunity, and they contribute to the initiation of adaptive immunity by recruiting other immune cells 34 . Recent studies have confirmed that macrophages were involved in anti-inflammatory processes and bone remodeling 35 , 36 . In this study, we found that ASA treatment inhibited macrophage polarization to the LPS-induced macrophages.…”
Section: Discussionmentioning
confidence: 94%
“…These results are consistent with other reports of overexpression in the microglia of genes associated with inflammation response in response to an inflammatory challenge. 63,64 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the many similarities between microglia and macrophages, there are a few reports regarding cell type specific gene transcription mechanisms in these tow cell types (Durafourt et al 2012; Lee et al 2014). There are also several reports using bone marrow chimera model obtained by transplantation of lethally irradiated recipients to distinguish the microglia to macrophages (Tang et al 2012b; Evans et al 2014).…”
Section: Introductionmentioning
confidence: 99%